ANALISIS PENGARUH KEPEMILIKAN INSTITUSIONAL DAN GROWTH TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR PERTANIAN YANG TERDAFTAR DI BEI TAHUN 2013-2017 - Alim Hakim (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aimed to analyze the influence of institutional ownership and growth to firm value with capital structure as an intervening variable in agriculture companies listed on the Indonesia Stock Exchange in 2013-2017, with a research sample 19 companies using path analysis. The results of the study showed that institutional ownership had negative and significant effect on capital structure and firm value, growth has no significant effect on capital structure and firm value, capital structure has no significant effect on firm value, and capital structure can not mediate institutional ownership and growth of firm value.